(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Ethics in workplace guarantees positive environment to the employees. It is often seen that an organisation where there is positive atmosphere the employees are often happy and contented. Such workplaces are seen as offices where employees look forward to come to work, unlike other places where office is a mere burdensome routine. Positively ethical organisations emit positivity leading to loyal employees and low attrition rates. Such employees are more attached towards the organisation. On the other hand professionalism means the conduct or key qualities that exemplify a certain profession or a professional being. Professionalism states that there is a certain level of workmanship or professional duties. Professionalism means being successful ethically and also influencing co-workers.